Deriving a prototype for the dynamic generation of learning path in an e-learning environment using genetic algorithm. (1st January 2013) - Anitha, D.; Deisy, C.
E-learning has been regarded as the future education and focused by many research works to improve its intelligence and effectiveness as a knowledge-based system. Personalised e-learning, is one of such major issues in the field of knowledge-based e-learning systems. Teaching according to the ability and attitude of the learners is one of the major concerns of personalised e-learning. This research work proposes a new method for dynamic generation of learning path using genetic algorithm. This work recommends dynamic learning content, teaching methodology and assessments based on the learners' knowledge and attitude identified by Bloom's taxonomy.